KEBERMAKNAAN HIDUP PEKERJA SEKS KOMERSIAL DITINJAU DARI KONSEP DIRI - Purwaningtyastuti Purwaningtyastuti; Dian Savitri (Universitas Semarang, 2016)
This study aims to to test empirically a link between the concept of self with meaning life commercial sex workers.Subject in this research was commercial sex workers do in the Sunan Kuning SemarangData collection method in penelitan it used scale meaning life and scale of the concept of self .The subject of this research as many as 42 people .Analysis using correlation product moment .Hypothesis advanced by in research which is there are the relationship between the concept of self with meaning living on commercial sex workers The analysis result of the data shows that r xy = 0,301 and p = 0.053 ( p & lt; 0.05 ) so that hypothesis this research rejected .There was no connection between the concept of self with meaning life .The concept of self contributed to meaning life of 9,06 % , while 90,94 % influenced by other factors were not involved in this research